Hydrophilicity control of laser-induced amorphous carbon-encapsulated carbon nano-onions and their application to proton exchange membrane fuel cells under low humidity. (30th October 2021) - Yeon, Je Hyeon; Choi, Jiwoo; Jang, Segeun; Choi, Mansoo
Abstract: Proton exchange membrane fuel cells (PEMFCs) are operated in a range of different environments including near-dry operating conditions. When a PEMFC operates under low relative humidity (RH) conditions, performance degradation rapidly occurs because of the decreased ionic conductivity of dehydrated membrane electrode assemblies (MEAs). As such, securing additional water inside the MEA is important for achieving a high-performance PEMFC under low RH operating conditions. Herein, amorphous carbon-encapsulated carbon nano-onions (AC-CNOs) were prepared by laser pyrolysis method. The hydrophilicity of AC-CNOs varied on the basis of particle size, which affected the amount of oxygen functional groups attached to the amorphous carbon. To confirm the water retention effect of the AC-CNOs, three different catalysts were incorporated into the MEA of the anode electrode, and a Pt@AC–CNO–3 with an average AC-CNO size of ∼164 nm exhibited a significantly improved performance under low RH condition. Moreover, to achieve a synergetic effect from both the anode and cathode, an additional AC-CNO layer was introduced on the cathode catalyst layer. The dual-side MEA with the hydrophilic catalyst layer at the anode and an additional carbon covering layer at the cathode showed significantly increased performance relative to the reference MEA, i.e., >80.2% under RH44%@90 °C conditions. Graphical abstract: Image 1 Highlights: AC-CNOs are prepared by irradiating a laser to hydrocarbons flame capable of mass continuous production. The MEA with anode of Pt@AC–CNO–3, which is the most hydrophilic, shows the best performance under low humidity. The carbon covering layer with AC-CNO-1 on the cathode plays an important role in water retention. The synergistic effect of these layers significantly improves device performance under low humidity.